2013
DOI: 10.17509/ijal.v3i1.194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Gender-Bias in the Iranian Pre-University English Textbooks

Abstract: Textbooks can affect learners' attitudes, viewpoints, and their choice of language in second/foreign language (L2) communication. The various ways in which the people are displayed in communication may affect students' viewpoints. This study was an attempt to examine several potential areas of gender-bias in the representation of women and men in the pre-university English textbook, an English language teaching (ELT) textbook with two volumes taught in the high schools of Iran. To evaluate this textbook, conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A comparative analysis of gender stereotypes in the textbooks of two Arab countries found that textbooks in Jordan featured female characters 20.8 percent of the time as compared to almost zero or no mention of achievements of women in Palestine [ 71 ]. Likewise in Iran, some studies pointed out female exclusion and the quality of representation in the textbooks (e.g., [ 61 ] [ 72 74 ]). Bahman and Rahimi, for instance, examined different aspects of gender bias in 3 volumes of English textbooks taught in secondary schools in Iran [ 72 ] and found 70%-80% names, nouns, pronouns, and adjectives to be male specific.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A comparative analysis of gender stereotypes in the textbooks of two Arab countries found that textbooks in Jordan featured female characters 20.8 percent of the time as compared to almost zero or no mention of achievements of women in Palestine [ 71 ]. Likewise in Iran, some studies pointed out female exclusion and the quality of representation in the textbooks (e.g., [ 61 ] [ 72 74 ]). Bahman and Rahimi, for instance, examined different aspects of gender bias in 3 volumes of English textbooks taught in secondary schools in Iran [ 72 ] and found 70%-80% names, nouns, pronouns, and adjectives to be male specific.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies had been conducted in order to know the effectiveness of teachers and students' roles in the class (Rahimi & Hosseini Karkami, 2015;Soodmand Afshar, & Doosti, 2014;Mahmud, 2017Mahmud, , 2018. Gender issues in relation to English language teaching, have also been investigated recently (Mahmud, 2010;Roohani & Zarei, 2013;Viriya & Sapsirin, 2014). Many other studies had revealed the complicated problems faced by English learners in learning English (Serag, 2011;Krashen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An example of study was conducted by Puteh, Zin, & Ismail (2016), which confirmed that gender differences need to be given attention since "the difference between the girls and boys has been attributed to reading engagement among the students (p. 118). Therefore, gender differences are assumed to influence the choices of those learning strategies (Ehrman & Oxford, 1989;Oxford, 1990;Gurian, 2001;Severiens & Dam, 2005;Zhenhui, 2005;Logan & Johnston, 2009;Yilmaz, 2010;Park & French, 2011;Roohani & Zarei, 2013;Tam, 2013;Viriya & Sapsirin, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them was the issue of politeness in teacher and student interaction (Zena, Marlyna Maros & Nor Fariza Mohd Nor, 2012;Senowarsito, 2013). Gender issues in relation to English language teaching have also been investigated recently (Mahmud, 2010;Roohani & Zarei, 2013;Viriya & Sapsirin, 2014). 226 happenings in the classroom".…”
Section: Introductionmentioning
confidence: 99%